Analysing the Physical Quality of Reconstructed Residential Environment of Bam City - mahmod Ghadir; Soghra Shahrbabaki (تحقیقات کاربردی علوم جغرافیایی)
In developing countries, every year natural hazards causes major losses in urban and rural settlements. In this regard, it is noteworthy that in December 2004 bam earthquake caused widespread damages. With over 9 years passed of this crisis and reconstruction after that, it is important to assess the quality of reconstruction. So, the problem is that how is the physical quality of Bam that reconstructed. So, based on the theoretical framework, two hypotheses were offered. Then, based on the theoretical bases and previous studies, the operational definition of physical quality concept offered in three indexes and 40 indicators, and combined by AHP and SAW methods. Needed data gathered by households, experts and field questionnaires. For testing hypotheses used causal-comparative and correlation methods. Sample size calculated by Cochran's method (311 households). Sampling has done by cluster and random methods. Gathered data were analyzed by: One-way ANOVA and Tukey-test at first hypotheses; and correlations methods at second hypotheses. The results showed that the physical quality of reconstructed residential environment in Bam is different between various neighborhoods. Also, the results of correlation test showed that general physical quality have significant relation with literacy, income, occupation and socio-economic status at 99 percent of confidence. According to the findings, physical quality at society scale has socio-economical aspects. So, we must pay attention to this point seriously.